UHF RFID anti-collision algorithm based on blind separation and dynamic bit-slot grouping - Hua LI; Zhi-ping JIA; Hong-jun WANG; Ju LIU (Tongxin xuebao)
A novel ultra high frequency(UHF)radio frequency identification（RFID）anti-collision algorithm based on independent components analysis(ICA)and dynamic bit-slot grouping technology was proposed.The ICA algorithm was used for identifying several tags simultaneously.The dynamic bit-slot tags grouping technology was used for ensuring the number of tags read by a reader at the same time was less than or equal to its antennas’number,and enabling the ICA wouldn’t work in an underdetermined state.Theoretical analysis and simulated experimental results show that the tags identification rate of the proposed algorithm is far more than that of traditional stochastic or deterministic TDMA RFID anti-collision algorithms.